AN INVESTIGATION OF EARNINGS MANAGEMENT IN INDONESIAN MANUFACTURING INITIAL PUBLIC OFFERINGS - Gumanti, Tatang Ary (Gadjah Mada International Journal of Business, 2003)
This paper examines whether the issuers of Indonesian manufacturing initial public offerings (IPOs) manage the firms reported earnings by making income increasing discretionary accruals. The absence of market-determined prices for IPO shares prior to the offering has made issuers and underwriters to use nonprice information. The test was performed on a sample of 45 IPOs that went public during the period of July1991 through December 1994. The model used in this study follows the one developed by Friedlan (1994). The results show that there is no evidence that earnings management occurs among the sample firms. In other words, this study is unable to reject the null hypothesis that the issuers of Indonesian IPOs exercise accounting discretion that increases the reported earnings in the periods prior to the offering. In contrast, the study finds strong evidence of earnings management in the period after the offering, which could be interpreted as issuers trying to maintain the firms performance after the offering by making income increasing discretionary accruals.